Bacillus sp. SW14 isolated from arid mangroves sediments enhances tomato plant growth: insights from genome analysis and greenhouse evaluation - Sadaiappan, Balamurugan; Ali, Qurban; Afridi, Mahideen; Khan, Munawwar Ali; Mundra, Sunil (Frontiers in Plant Science, 2025)
Mangroves grow in arid regions with high temperatures, low precipitation, and evaporation. Despite low humidity and high salt concentration, these arid mangroves support diverse microorganisms, including salt-and temperature tolerant. The bacteria isolated from these arid mangroves have potential applications in arid agronomy, which alleviate plant stress and enhance plant growth. In this study, we characterize the genome of previously reported PGP and stress-tolerating bacteria, Bacillus sp. SW14, isolated from mangrove sediments of Umm Al Quwain, United Arab Emirates. Further, we investigated its effects on tomato seed germination and plant growth. Genome size of the strain SW14 is 4.25 MB, with a G+C content of 43.72%. Genome-based phylogenetic and ANI analyses confirmed strain SW14 as a novel Bacillus sp. The genome also consists of multiple PGP trait-related genes such as nitrogen fixation (nifSUM), ammonia production (glnAB, ureABCDE), phosphate (pqq, PhoADEHPRU, and pstABCS) and potassium solubilization (kch/mthK, trkAGH and ktrAB), Indole-3-acetic acid (IAA) (trpABCDEFS, iaaT/yedL/ysnE and yhcx) and siderophore (dhbABCEF) production. It also includes genes associated with salt and heat (GrpE, dnaJ, K and groL, S) stress tolerance and bactericidal and fungicidal genes. Greenhouse trial revealed that the inoculation of strain SW14 significantly improved tomato plant growth, increased leaf number (Control (C): 6.82 ± 3.21, Incubated (I): 20.51 ± 11.55), leaf fresh weight (C: 0.11 ± 0.044, I: 0.15 ± 0.0035), leaf surface area (C: 1.823 ± 0.144, I: 15.15 ± 4.13), shoot height (C: 4.56 ± 0.94, I: 10.54 ± 3.44), and average Soil-Plant Analysis Development (SPAD) values (C: 31.01 ± 1.46, I: 33.79 ± 1.68). Additionally, parameters such as chlorophyll a (C: 2.21 ± 0.84, I: 3.39 ± 0.51), total chlorophyll (a + b) (C: 3.33 ± 1.26, I: 4.91 ± 0.58), carotenoid (C: 0.81 ± 0.29, I: 4.70 ± 0.55) and total chlorophyll to carotenoid (C: 3.81 ± 1.38, I: 9.28 ± 1.28) in tomatoes inoculated with the strain SW14 were increased. In conclusion, Bacillus sp. SW14 is a promising candidate for supporting plant growth in arid agroecosystems since it possesses a variety of PGP genes and the ability to thrive in high temperatures and salinity conditions.